Agility and flexibility in international business research: A comprehensive review and future research directions - Christofi, Michael; Pereira, Vijay; Vrontis, Demetris; Tarba, Shlomo; Thrassou, Alkis (My University, 2021)
This study explores 134 articles on agility and flexibility research published in the top-nine international business (IB) journals. Accordingly, we critically analyze, map and structure flexibility and agility research in IB, and synthesize the findings into an integrative framework. The paper identifies a wide range of definitions of the concept and a lot of work on its conceptualization. However, studies at the individual and institutional levels of analyses are scarce, and the concept is under-theorized, as there is a dearth of real theoretical underpinnings in this research stream. Thus, in addressing this gap, more qualitative and interdisciplinary research is needed.
Keywords: Agility; Flexibility; International business research; Systematic review